Ebenezer African Methodist Episcopal Church - (:unkn) unknown (Valdosta State University Archives and Special Collections, 2008)
This item pertains to Ebenezer African Methodist Episcopal Church in Grady County, Georgia, and is part of the Churches series within the Grady County Historical Society Collection. It includes newspaper clippings, an announcement of the church's listing in the National Register of Historic Places, photographs, handwritten accounts of church history, a list of pastors, and handwritten letters. The original materials are held by the Grady County Historical Society and were provided to Valdosta State University Archives and Special Collections for digitization and online access.
1 PDF document, 70 scans
Keywords: Grady County (Ga.); History-Societies, etc.; Church Records and registers; Church History